The Effect of Learning Resources and Learning Motivation on Subject Learning Outcomes Financial Accounting Class XI AKL - Richardo Haholongan Nadeak; Anggun Tiur Ida Sinaga; Susy Alestriani Sibagariang (Jurnal Pendidikan, Sains Sosial, dan Agama, 2024)
The problem in this research is the low learning outcomes of students in the Financial Accounting subject, which is suspected to be influenced by the lack of learning resources as well as low student learning motivation. This research aims to determine the influence of learning resources and learning motivation on the learning outcomes of Financial Accounting for Class XI AKL students at SMK Negeri 1 Pematangsiantar. The type of research is quantitative research with a descriptive method. The research population consists of all students from Class XI AKL1, XI AKL2, and XI AKL3, totaling 94 students, using a saturated sampling technique. Before conducting multiple linear regression analysis, classical assumption tests were performed. The normality test results indicate that the data is normally distributed with a significance value of 0.200 > 0.05. The multicollinearity test shows no multicollinearity symptoms because the Tolerance value > 0.10 and VIF < 10. The heteroscedasticity test shows no specific pattern as the scatter of points is random. The t-test results indicate that learning resources have a positive and significant influence on student learning outcomes (t_calculated = 4.765 > t_table = 1.98638). Similarly, student learning motivation has a positive and significant influence on learning outcomes (t_calculated = 2.852 > t_table = 1.98638). The F-test results show that both variables simultaneously have a significant influence on student learning outcomes (F_calculated = 36.632 > F_table = 3.10). The coefficient of determination (R²) value of 0.446 indicates that 44.6% of the variation in student learning outcomes is influenced by the understanding of the MYOB Accounting application and learning interest, while the remaining 55.4% is influenced by other factors not examined in this research.